The Pharmacokinetic and Biopharmaceutical Effect of Ascorbic acid (Vitamin C) on Pefloxacinon Concurrent Administration in Human - Awofisayo SO, Umoren FJ, Uwanta EJ (Journal of Applied Pharmaceutical Science)
The aim of the study was to assess the pharmacokinetic and biopharmaceutical effect of ascorbic acid (Vitamin C) on pefloxacin on concurrent administration in man through urine excretion data and microbiological evaluation. A two way crossover study was performed in ten healthy male volunteers aged (Mean ± SD) 45 ± 5.5 years and weight (Mean ± SD) 75.4 ±12.5 Kg recruited and given pefloxacin 400mg as single dose and urine samples collected and pooled up at time intervals. The drug was concurrently given with 500mg vitamin C after a washout period of 4 weeks and urine samples similarly collected. Urine samples collected were analyzed and pefloxacin concentrations were determined with UV spectrophotometer from a validated calibration curve. The pharmacokinetic parameters Cmax, tmax, Ke and t1/2 were determined and compared. Microbial evaluation of the interaction of the drugs was performed through MIC determination using urinary isolate S. aureus (U-11420). The ke for pefloxacin alone was significantly lower than that for pefloxacin concurrently administered with vitamin C (0.1hr-1 and 0.3hr-1) P< 0.05. The amount of pefloxacin excreted was significantly lower onsingle administration of pefloxacin compared to the co-administration with vitamin C, (44.13mg against 141.99mg) at P< 0.05. The MIC obtained against S. aureus was 0.025mg/mlfor pefloxacin alone while the co-solution with vitamin C at below 2hr and 4hr impregnation period was 0.05mg/ml and 0.1mg/ml respectively. There was significant chemical, microbiological and biopharmaceutical interaction on co-administration of pefloxacin with vitamin C.
Keywords: Pefloxacin,vitamin C,Co-administration,Biopharmaceutical interaction.